Stability and Existence of Periodic Solutions for Cellular Neural Networks with State Dependent Delays on Time Scales - Yaping Ren; Yongkun Li (Discrete Dynamics in Nature and Society)
We study delayed cellular neural networks on time scales. Without assuming the boundedness of the activation functions, we establish the exponential stability and existence of periodic solutions. The results in this paper are completely new even in case of the time scale 𝕋=ℝ or ℤ and improve some of the previously known results.